Estrogen maintains trabecular bone volume in rats not only by suppression of bone resorption but also by stimulation of bone formation. - J Chow; J H Tobias; K W Colston; T J Chambers (The Journal of Clinical Investigation, 1992)
Estrogen is generally considered to maintain bone mass through suppression of bone resorption. We have previously demonstrated that administration of pharmacologic doses of estrogen increases bone formation in ovary-intact rats. To assess the effects of physiological concentrations of estrogen on bone formation, estrogen was administered to ovariectomized rats in which bone resorption was suppressed by the bisphosphonate 3-amino-1-hydroxypropylidene-1-bisphosphonate (AHPrBP). Animals receiving exogenous 17 beta-estradiol (E2) (1, 10, and 100 micrograms/kg daily for 17 d) showed a dose-dependent increase in trabecular bone volume of 1.9, 25.8, and 43.6%, respectively, compared with those rats treated with AHPrBP alone. The increase in bone volume was associated with an increase in bone formation in E2-treated animals, in which bone resorption had been almost completely suppressed by AHPrBP. Neither ovariectomy, AHPrBP, nor E2 treatment had a significant effect on the volume or rate of formation of cortical bone. Thus, the increased bone resorption, which is a consequence of estrogen-deficiency, entrains increased bone formation, which masks a simultaneous reduction in estrogen-dependent bone formation. Therefore, in addition to the nonspecific effect of estrogen to depress formation via coupling, we have identified a specific effect of estrogen to increase formation independent of coupling. Thus it appears that estrogen maintains bone volume not only through inhibition of bone resorption, but also through stimulation of bone formation. Images